(untitled) (Annals of Medical Research, 2023)
Aim: To assess the preoperative and operative findings and postoperative early and late complications in patients who were operated on electively and to compare the factors affecting these results through open and laparoscopic hernia techniques. Materials and Methods: In this retrospective study, the patients were initially divided into two groups as open inguinal hernia repair (OIHR) and laparoscopic inguinal hernia repair (LIHR); then the LIHR group was divided into two subgroups as transabdominal preperitoneal (TAPP) and total extraperitoneal (TEP) groin hernia repair with respect to the operation techniques. Preoperative, operative, and early and sixth-month late-period complications of the patients were statistically analyzed. Results: In a total of 241 patients included in the study, 170 patients were included in the OIHR group, and 71 patients were included in the LIHR group (TAPP=20, TEP=51). No statistically significant difference was noted between the OIHR and LIHR groups and between the TAPP and TEP subgroups in terms of chronic pain, paraesthesia, and recurrence. Conclusion: We believe that there is no difference in long-term results between open and laparoscopic elective inguinal hernia surgery.